2002
DOI: 10.21273/jashs.127.4.484
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Fusion of Citrus sp. Microprotoplasts

Abstract: Large-scale production of microprotoplasts from `Ruby Red' grapefruit (Citrus paradisi Macf.) and from the Citrus L. sp. relative Swinglea glutinosa (Blanco) Merr., was performed after treatment of suspension cells with APM. An average of 75.2% of the microprotoplasts contained a single chromosome, followed by 17.1% with two, 4.6% with three, and 2.0% with four. Only 1.1% had more than five chromosomes. Maximum chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(32 reference statements)
1
8
0
1
Order By: Relevance
“…1 was mainly composed of microprotoplasts. This 2-band separation is similar to previous reports using sucrose gradients (Bracha and Sher, 1981), but different from those utilizing Percoll gradients in which several bands were produced (Ramulu et al, 1993;Louzada et al, 2002). The microprotoplasts were different in size and could be categorized into 3 groups, smaller than 5 mm, 5-10 mm and larger than 10 mm (Fig.…”
Section: Isolation Of Microprotoplasts From Micronucleated Protoplastssupporting
confidence: 85%
See 2 more Smart Citations
“…1 was mainly composed of microprotoplasts. This 2-band separation is similar to previous reports using sucrose gradients (Bracha and Sher, 1981), but different from those utilizing Percoll gradients in which several bands were produced (Ramulu et al, 1993;Louzada et al, 2002). The microprotoplasts were different in size and could be categorized into 3 groups, smaller than 5 mm, 5-10 mm and larger than 10 mm (Fig.…”
Section: Isolation Of Microprotoplasts From Micronucleated Protoplastssupporting
confidence: 85%
“…It has been suggested that the inhibition of spindle formation through microtubule-directed toxins, such as amiprophos-methyl (APM), cremart or oryzalin, can prevent metaphase chromosomes from separating into chromatids, thereby leading to micronucleation (Morejohn et al, 1987;Ramulu et al, 1988aRamulu et al, , 1990Ramulu et al, , 1994Verhoeven et al, 1990;Binsfeld et al, 2000;Saito and Nakano, 2001). So far, microprotoplasts have been successfully isolated from Solanum tuberosum (Ramulu et al, 1994;Rutgers et al, 1997;Matthews et al, 1999), Nicotiana plumbaginifolia Ramulu et al, 1993), Helianthus giganteus, H. maximiliani (Binsfeld et al, 2000), Swinglea glutinosa, Citrus grandis (Louzada et al, 2002), Hemerocallis hybdrida (Saito and Nakano, 2002b), and Lilium longiflorum (Saito and Nakano, 2002a,c). In addition, it has been reported that a combined treatment with a spindle toxin and a DNA-synthesis inhibitor, such as hydroxyurea (HU) that induces cell synchronization, can significantly increase the rate of micronucleation (Ramulu et al, 1993;Saito and Nakano, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two principal fusion methods to achieve CMS transfer. The first is by asymmetric protoplast fusion using irradiated protoplasts as a donor parent and chemically inactivated protoplasts as the recipient parent (Melchers et al 1992;Sigareva and Earle 1997), and the second is by cytoplast-protoplast or microprotoplast fusion (Sakai and Imamura 1990;Spangenberg et al 1991;Louzada et al 2002). It is generally difficult to generate highly asymmetric hybrids or cybrids by asymmetric fusion, and the cytoplast-protoplast or microprotoplast fusion method is even more technically difficult (see above-mentioned references).…”
Section: Introductionmentioning
confidence: 99%
“…This proved that there is no requirement of designed pressure to maintain donor chromosomes in the recipient background. In citrus, microprotoplast isolation was first accomplished by Louzada et al [51] and embryos of sweet orange containing a few additional chromosomes from sour orange were obtained. The presence of a high concentration of cytochalasin B was later determined to be the cause of non-regeneration of embryos (unpublished data).…”
Section: Figure 102mentioning
confidence: 99%